Application of a Communicative Approach in Teaching Regional Languages: Impact on the Maintenance and Development of Regional Languages in Tasikmalaya City: Application of a Communicative Approach in Teaching Regional Languages: Impact on the Maintenance and Development of Regional Languages in Tasikmalaya City - Ratnasari, Dewi (International Journal of Linguistics, Communication, and Broadcasting, 2023)
This research explores the teaching of regional languages using a communicative approach. Language instruction encompasses various aspects, including the nature and function of teaching materials, learning objectives, the selection and development of teaching aids, the creation of learning experiences, instructional media and resources, and evaluation models. The communicative approach in teaching regional languages emphasizes the importance of language as a tool for communication with diverse variations. The primary goal of language instruction is to cultivate proficient communication skills tailored to students' needs in real-life interactions. To achieve this objective, it is crucial to employ authentic discourse materials that enable students to engage in meaningful communicative situations, use language in relevant contexts, and explore various language varieties. Students' learning experiences should also be supported by suitable media and learning resources, including the use of teaching materials that allow students to interact directly with the language being learned. Learning assessments should encourage students to actively practice language skills and stimulate continuous communicative performance. The implementation of the communicative approach in teaching regional languages will lead to an understanding of language as a system for conveying messages with communicative functions. This approach promotes the use of diverse regional language varieties and shifts the focus from language form and structure. As a result, an environment for the use of regional languages can be established or preserved, even as a replacement for the diminishing use of regional languages within families undergoing changes. Thus, the communicative approach in teaching regional languages holds the potential to strengthen and preserve regional languages in the context of cultural diversity.